Tubulopapillary Carcinoma of the Mammary Gland in a Mare - Ferreira Júnior, Jair Alves; Pavarini, Saulo Petinatti; dos Santos, Marilúcia Campos; Alvarenga, Karla; Ocampos Pedroso, Pedro Miguel; Almeida e Macêdo, Juliana Targino Silva (Acta Scientiae Veterinariae, 2019)
Background: Mammary gland neoplasia are often observed in bitches and cats, rarely in cows, goats, sheep, sows, and mares. Among the neoplasia that affect mares, breast tumors are rare, as they occur more frequently in older animals. In horses, mammary gland tumors occur more frequently in older animals. In this species there are reports of cases describing carcinomas and adenocarcinomas and several subtypes. Mammary neoplasms in equines tend to be locally aggressive and promote metastases to the regional lymph nodes and other organs, including the lungs, and may cause pleural effusion. The aim objective of the present case report was to describe the clinical-pathological and immunohistochemical findings of a tubulopapillary carcinoma of the mammary gland in mare. Case: Was received a biopsy of a tumor mass of the mammary gland of a 15-year-old Quarter Horse mare. According to the veterinarian, the mare presented an increase in volume with ulceration of the mammary gland three months before the biopsy. Macroscopically, the mass was firm to the cut with white surface measuring 12x12 cm. The fragment was fixed in 10% formalin, routinely processed for histology, paraffin embedded, and stained with hematoxylin and eosin. Microscopically, we observed proliferation of epithelial neoplastic cells arranged in tubules and papillary projections, some with two to three layers of cells. Neoplastic cells had oval, moderate and distinct cytoplasm. The nuclei were rounded with dense chromatin and an apparent nucleolus. There were two figures of mitosis per field of high magnification. Proliferation of neoplastic cells invaded adjacent tissues, and in lymph vessels of the region, neoplastic cells were observed as well as inflammation in adjacent tissue. In addition, the breast fragment was submitted to the immunohistochemistry technique using anti-pancytokeratin and anti-vimentin antibody. In immunohistochemistry for pancytokeratin, there was immunoreactivity with marked cytoplasm in neoplastic epithelial cells. In immunohistochemistry for vimentin, there was cytoplasmic labeling in cells of the supporting tissue (fibroblasts and endothelial cells). After approximately six months of the initial diagnosis, the mare died. Discussion: The diagnosis of tubulopapillary carcinoma of the mammary gland in a mare was based on the clinical-pathological and immunohistochemical findings. In mares, descriptions of breasts neoplasia are uncommon and found in animals aged over 12 years. In a study carried out in slaughterhouses in France, with approximately 40,000 horses slaughtered, only 45 breast neoplasms (0.11%) were observed, most of them consisting of carcinomas. In these equines, the absolute incidence of neoplasia of the reproductive system increases with age and tumors generally appear as deep, multifocal, and ulcerating skin nodules. Thus, important differential diagnoses include chronic mastitis and prepartum breast edema. In mares with neoplasia of the mammary gland, unilateral or bilateral volume increase, pain, warm area, redness and suppurative serous discharge are frequently observed. There are also reports of skin ulceration or necrosis. In the present report, the mare showed increased volume of the mammary gland, with focal hyperthermia, fistulated area and serum-blood secretion. The literature suggests a reserved prognosis for any mare presenting mammary neoplasia. Histopathology and immunohistochemistry were fundamental for the diagnosis of tubulopapillary carcinoma of the mammary gland in the present study. Mammary neoplasiss in mares are rare, but should be considered in the diagnosis of mammary pathologies in this species.